Irreversibilities and the optimal timing of environmental policy under Knightian uncertainty - Takao Asano (Osaka University, Institute of Social and Economic Research (ISER), 2005)
In this paper, we consider a problem in environmental policy design by applying optimal stopping rules. The purpose of this paper is to analyze the optimal timings at which the government should adopt environmental policies to deal with increases in greenhouse gas concentrations and to reduce emissions of SO2 or CO2 under the continuous-time Knightian uncertainty. Furthermore, we analyze the effects of increases in Knightian uncertainty on optimal environmental policies and the reservation value.
Keywords: D81; H23; L51; Q23; 330; Knightian Uncertainty; Environmental Policy; Irreversibilities; Umweltpolitik; Zeit; Risiko; Klimawandel; Theorie